2011
DOI: 10.1007/s00213-011-2198-3
|View full text |Cite
|
Sign up to set email alerts
|

Stimulant effects of adenosine antagonists on operant behavior: differential actions of selective A2A and A1 antagonists

Abstract: Rationale Adenosine A2A antagonists can reverse many of the behavioral effects of dopamine antagonists, including actions on instrumental behavior. However, little is known about the effects of selective adenosine antagonists on operant behavior when these drugs are administered alone. Objective The present studies were undertaken to investigate the potential for rate-dependent stimulant effects of both selective and nonselective adenosine antagonists. Methods Six drugs were tested: two nonselective adenos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 72 publications
2
27
0
Order By: Relevance
“…Caffeine also increased both reinforced responding and non-reinforced responding, and this agrees with evidence for caffeine-induced stimulation of low response rates under other circumstances, such as the early segments of intervals from fixed-interval schedules of food-maintained responding (McMillan, 1979; Michaelis, Holloway, Bird, & Huerta, 1987; Randall et al, 2011; Spealman, 1988; Valdes, et al, 1982). However, in contrast to the effects of amphetamine, the response increasing effects of caffeine on both reinforced and non-reinforced responding were characterized by an inverted-U shaped dose-effect curve, and peak increases in reinforced and non-reinforced responding were smaller than those produced by amphetamine or cocaine.…”
Section: Discussionsupporting
confidence: 83%
“…Caffeine also increased both reinforced responding and non-reinforced responding, and this agrees with evidence for caffeine-induced stimulation of low response rates under other circumstances, such as the early segments of intervals from fixed-interval schedules of food-maintained responding (McMillan, 1979; Michaelis, Holloway, Bird, & Huerta, 1987; Randall et al, 2011; Spealman, 1988; Valdes, et al, 1982). However, in contrast to the effects of amphetamine, the response increasing effects of caffeine on both reinforced and non-reinforced responding were characterized by an inverted-U shaped dose-effect curve, and peak increases in reinforced and non-reinforced responding were smaller than those produced by amphetamine or cocaine.…”
Section: Discussionsupporting
confidence: 83%
“…With the availability of selective A 2A receptor ligands, a large number of experiments demonstrated that A 2A receptor agonists and antagonists induce the same qualitative psychomotor depressant and activating effects that D 2 receptor antagonists and agonists, respectively; (Ferré et al 1991c; Kanda et al 1994; Rimondini et al 1997; Shiozaki et al 1999; Randall et al 2011; Nunes et al 2013); that A 2A receptor agonists and antagonists selectively counteract and potentiate the psychomotor activating effects of D 2 receptor agonists, respectively (Popoli et al 1996; Rimondini et al 1998; Stromberg et al 2000; Ferré et al 2001); but also, that selective A 2A , but not A 1 , receptor antagonists counteract the psychomotor depressant effects of reserpine and D 2 receptor antagonists (Kanda et al 1994; Shiozaki et al 1999; Pardo et al 2012; Nunes et al 2013; Minor and Hanff 2015). Initial studies dealt mostly with locomotor activity recording, but more recent studies about the psychomotor activating effects of caffeine also dealt with measures of specific reward-oriented behavior, with caffeine and A 2A receptor antagonists increasing the responsiveness to specific rewarding stimuli, such as those associated with regular food (Randall et al 2011; Nunes et al 2013), sucrose solutions (Brianna Sheppard et al 2012) and those eliciting maternal behavior (Pereira et al 2011) and intracranial self-stimulation (Lazenka et al 2015).…”
Section: Psychomotor Activating Effects Of Caffeine: the Striatal Adementioning
confidence: 99%
“…Initial studies dealt mostly with locomotor activity recording, but more recent studies about the psychomotor activating effects of caffeine also dealt with measures of specific reward-oriented behavior, with caffeine and A 2A receptor antagonists increasing the responsiveness to specific rewarding stimuli, such as those associated with regular food (Randall et al 2011; Nunes et al 2013), sucrose solutions (Brianna Sheppard et al 2012) and those eliciting maternal behavior (Pereira et al 2011) and intracranial self-stimulation (Lazenka et al 2015). Lastly, A 2A but not A 1 receptor antagonists induce sensitization to their psychomotor-activating effects and cross-sensitization to caffeine (Hsu et al 2009, 2010).…”
Section: Psychomotor Activating Effects Of Caffeine: the Striatal Adementioning
confidence: 99%
“…In contrast to the 8-unsubstituted xanthine derivatives ( 1-4 ), which exhibit acceptable to good water-solubility, the 8-styrylxanthines ( 5-7 ) are relatively insoluble in water. Therefore, water soluble prodrugs of MSX-2 have been developed, such as the phosphate prodrug MSX-3 ( 7a : Hockemeyer et al, 2004) and the L -valine ester prodrug MSX-4 ( 7b : Vollmann et al, 2008), which represent very valuable pharmacological tools, particularly for in vivo studies ( e.g ., Randall et al, 2011; Collins et al, 2010; Mott et al, 2009; Bilkei-Gorzo et al, 2008; Schindler et al, 2005; Blum et al, 2003; Hauber et al, 1998). These drugs are very water-soluble but readily cleaved by enzymatic hydrolysis.…”
Section: Figurementioning
confidence: 99%